2015
DOI: 10.1007/s00436-015-4605-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of mini-FLOTAC and FLOTAC with classic methods to diagnosing intestinal parasites of dogs from Brazil

Abstract: Dogs may be affected by different species of gastrointestinal parasites which present great importance in veterinary medicine and public health. Several techniques to diagnosing these parasites have been proposed, but different performances achieved by each method make difficult the choice of the best technique to be used. In this study, the performance of two classic methods (i.e., Willis and Hoffman techniques) and two recent techniques (i.e., FLOTAC and Mini-FLOTAC) to diagnosing gastrointestinal parasites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 16 publications
2
13
0
4
Order By: Relevance
“…Additionally egg reduction was measured at day 23 following treatment with fenbendazole, since egg counts after a brief decline, continually increased until this day. All FEC were performed in triplicate using the Mini-FLOTAC (University of Naples Federico II, Naples, Italy) procedure with a detection threshold of 5 EPG (Lima et al, 2015; Maurelli et al, 2014), adding two grams of feces to 18 ml of sodium nitrate (Feca-Med ® , Vedco, Inc. St. Joseph; MO, USA specific gravity = 1.2). Fecal egg count reduction was calculated using the following formula: ((Pre-treatment FEC – Post-treatment FEC) / (Pre-treatment FEC)) x 100.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally egg reduction was measured at day 23 following treatment with fenbendazole, since egg counts after a brief decline, continually increased until this day. All FEC were performed in triplicate using the Mini-FLOTAC (University of Naples Federico II, Naples, Italy) procedure with a detection threshold of 5 EPG (Lima et al, 2015; Maurelli et al, 2014), adding two grams of feces to 18 ml of sodium nitrate (Feca-Med ® , Vedco, Inc. St. Joseph; MO, USA specific gravity = 1.2). Fecal egg count reduction was calculated using the following formula: ((Pre-treatment FEC – Post-treatment FEC) / (Pre-treatment FEC)) x 100.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of coccidian species in pets may vary widely depending on the technique used. It is important to note that the present study used the FLOTAC technique, which is a tool that presents high sensitivity in relation to the classical methods (LIMA et al, 2015). The high percentage of positivity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a reliable tool known as the FLOTAC technique has been used to diagnosing intestinal parasites of animals and humans (CRINGOLI et al, 2010;CRINGOLI et al, 2013). It has been demonstrated that this diagnostic method presents high sensitivity for detecting eggs and/or oocysts of parasites in several species of animals (RINALDI et al, 2011;LIMA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The procedure involves the dilution of 1 g of feces in a preservative solution, followed by filtration and addition of a solution for the flotation of parasitic structures using a specific apparatus developed for the technique. This technique evaluated several flotation solutions (FS) at variable densities and verified the recovery and quantification of several helminth species in humans and animals 41,105 . The FLOTAC technique was compared with conventional quantification techniques and was shown to be efficient with superior results for sensitivity 29,60,82,106,107 but did not demonstrate the same performance in protozoan infections 71,83,108 .…”
Section: /9mentioning
confidence: 98%